A man of his own [large type] - Wilson, Susan, 1951- (Thorndike Press, 2013)
Once a promising, professional baseball player, Rick Stanton returns from World War II with his body broken, and his dreams shattered. He and his wife, Francesca, had also volunteered their beloved dog, Pax, for the Army's K-9 Corp. Then the soldier who fought the war by his side returns with Pax, hoping to adopt him. Instead, the Stantons offer him a job as Rick's live-in aide. An unlikely family is formed, with Pax at its center.